2-thio-6-azauridine inhibits Vpu mediated BST-2 degradation. Issue 1 (December 2016) - Zhang, Quan; Mi, Zeyun; Huang, Yuming; Ma, Ling; Ding, Jiwei; Wang, Jing; Zhang, Yongxin; chen, Yang; Zhou, Jinming; Guo, Fei; Li, Xiaoyu; Cen, Shan
Abstract Backgroud BST-2 is an interferon-induced host restriction factor that inhibits the release of diverse mammalian enveloped viruses from infected cells by physically trapping the newly formed virions onto the host cell surface. Human Immunodeficiency Virus-1 (HIV-1) encodes an accessory protein Vpu that antagonizes BST-2 by down-regulating BST-2 from the cell surface. Results Using a cell-based ELISA screening system, we have discovered a lead compound, 2-thio-6-azauridine, that restores cell surface BST-2 level in the presence of Vpu. This compound has no effect on the expression of BST-2 and Vpu, but inhibits Vpu-mediated BST-2 down-regulation and exerts no effect on Vpu-induced down-regulation of CD4 or KSHV K5 protein induced BST-2 down-regulation. 2-thio-6-azauridine suppresses HIV-1 production in a BST-2-dependent manner. Further results indicate that 2-thio-6-azauridine does not interrupt the interaction of BST-2 with Vpu and β-TrCP2, but decreases BST-2 ubiquitination. Conclusion Our study demonstrates the feasibility of using small molecules to target Vpu function and sensitize wild type HIV-1 to BST-2-mediated host restriction.